2011
DOI: 10.1007/s10103-011-1028-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-level laser therapy on cochlear hair cell recovery after gentamicin-induced ototoxicity

Abstract: Cochlear hair cells are the sensory receptors of the auditory system. It is well established that antibiotic drugs such as gentamicin can damage hair cells and cause hearing loss. Rescuing hair cells after ototoxic injury is an important issue in hearing recovery. Although many studies have indicated a positive effect of low-level laser therapy (LLLT) on neural cell survival, there has been no study on the effects of LLLT on cochlear hair cells. Therefore, the aim of this study was to elucidate the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 16 publications
0
43
0
Order By: Relevance
“…Determination of whether NIR prevents gentamicin from inhibiting these enzymes or, on the contrary, results in a limitation of ROS production rate will require further investigation. Previous studies showed that PBM increase survival of cochlear hair cell numbers and mediates their recovery after acoustic or gentamicin-induced trauma in rats in vivo [66,67]. However, recovery is only partial and mainly benefits cells in the middle turn of the cochlea [67], yet the mechanism driving oxidative stress and modulating inflammatory pathways remain unclear.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Determination of whether NIR prevents gentamicin from inhibiting these enzymes or, on the contrary, results in a limitation of ROS production rate will require further investigation. Previous studies showed that PBM increase survival of cochlear hair cell numbers and mediates their recovery after acoustic or gentamicin-induced trauma in rats in vivo [66,67]. However, recovery is only partial and mainly benefits cells in the middle turn of the cochlea [67], yet the mechanism driving oxidative stress and modulating inflammatory pathways remain unclear.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies showed that PBM increase survival of cochlear hair cell numbers and mediates their recovery after acoustic or gentamicin-induced trauma in rats in vivo [66,67]. However, recovery is only partial and mainly benefits cells in the middle turn of the cochlea [67], yet the mechanism driving oxidative stress and modulating inflammatory pathways remain unclear. Our investigation introduces a better understanding of the mechanistic feature of NIR applied to cochlear hair cells and show that NIR reduces ROS, and suppresses proinflammatory mediators.…”
Section: Discussionmentioning
confidence: 97%
“…Since LLLT was effective in vitro study, it was expected to be effective in vivo study as shown in this study.LLLT has been shown to be effective in the treatment of gentamicininduced ototoxicity. 5 The presently demonstrated positive results on vestibular ototoxicity may provide further clinical application of LLLT. Further studies are required to demonstrate the efficacy of delayed treatments on chronic vestibulopathy and for detailed understandings of its mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…4 LLLT has been effective to prevent and recover cochlear hair cells after gentamicin ototoxicity in vitro study. 5 LLLT has been effective to recue noise induced hearing loss in rats. 6 However, no study in the literature has investigated the effect of LLLT on the recovery of vestibular dysfunction and damaged vestibular hair cells after ototoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that therapeutic effects of low-level light radiation are dependent on the selected frequency and intensity of external exposures as well as absorption of such irradiation by molecules and cells [7,28,32]. Typical irradiation intensity range used in LILT is between 10 and 5000 mW/cm2 [9,17].…”
Section: Introductionmentioning
confidence: 99%